Responding to Polarization and Division: The Mission of the Indian Church Today - Thomas, P. Lawrence (Asian Horizons, 2025)
This article explores the mission of the Indian Church in an era marked by political polarisation, religious nationalism, and social division. It underscores the challenges arising from the perception of Christianity as a foreign import and the current socio-political environment that marginalises religious minorities. The author suggests both outward strategies—such as adopting a low profile, enhancing social responsibility, and building mutual relationships—and inward approaches, including cultural translation of the Gospel, personal holiness, and community development. Emphasising holistic engagement and sustainable witness, the article advocates for a renewed, contextually aware mission that mirrors the resilience and integrity of the early Church.